Pengaruh Citra Merek dan Electronic Word of Mouth Terhadap Keputusan Penggunaan Pada Marketplace Lazada di Kabupaten Buleleng - Yuliastuti, Luh Mega; Susila, Gede Putu Agus Jana (Universitas Pendidikan Ganesha, 2021)
This research aims to examine the effect of brand image and electronic word of mouth on purchasing decisions at Lazada marketplaceÂ in Buleleng Regency, both simultaneously and partially. The framework used in this researchs is causal quantitative. Sample is determined by using purposive sampling technique. Data were collected by using a questionnaire which will be tested for its realiability and validity, and will be analyzed by multiple linear regression analysis. The results of this research indicate that (1) brand image and electronic word of mouth have a simultaneous effect on purchasing decisions, (2) brand image has an effect on purchasing decisions, (3) electronic word of mouth has an effect on purchasing decisions at Lazada marketplaceÂ in Buleleng Regency.